La prensa y el discurso político en la historia peruana: algunas consideraciones teóricas y metodológicas - Morán, Daniel (2008)
The shaped discourse within the pages of the written press represents the ideas, opinions, arguments and interests of greater importance of the society which produces it. In this way, the study of each one of the printed pages in the history of Peru is fundamental to understand the development and the historical process by which our country has passed. In that sense, through this investigation it has made a critical and reflective analysis of the press, its discourse and the relation that maintains with the political power. As well as, we propose a theoretical and methodological model which can provides a better systematization and utilization when rebuilding the Peruvian history.